The Legal Impact of Agrarian Conflicts in The PIK2 National Strategic Project on Local Community Rights - Rita Alfiana; Dahyono Dahyono (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The disharmony between the legal basis of the PIK2 National Strategic Project (PSN PIK2) and the legal regulations above it indicates a conflict of interest between the parties involved. The 1945 Constitution states that all things in the Indonesian archipelago, including their contents, are controlled and managed by the state for the benefit and welfare of all its people. The acquisition of 1,755 hectares of land for the Tropical Coastland megaproject of PSN PIK2, located in Muara Village, Kronjo Village, Tanjung Pasir Village, and Kohod Village, has resulted in the loss of land rights for local communities. The Supreme Court through decision No. 12 P/HUM/2025, stated that the Coordinating Minister for Economic Affairs Regulation No. 12/2024 concerning the Sixth Amendment to the Coordinating Minister for Economic Affairs Regulation No. 7/2021 concerning Amendments to the PSN List, is in conflict with higher laws and regulations, namely Article 3 paragraph (4) PP 42/2021, Article 8 of Law 41/1999, Article 1 number 16 and 17 of Law 32/2009 and Article 1 number 28 of Law 26/2007. Through the Statute approach and Case approach, this study aims to seek justice and legal certainty for affected local communities, as well as provide solutions so that national development does not become an agrarian conflict.